Flying machine - Nahum, Andrew (New York : DK Pub., 2004)
A photo essay tracing the history and development of aircraft from hot-air balloons to jetliners. Includes information on the principles of flight and the inner workings of various flying machines.
At head of title: Eyewitness.
Includes index.
Keywords: Flying-machines -- Juvenile literature; Flying machines; Aeronautics -- History